AlScN device with low working voltage and low leakage current and preparation method thereof
By using a low-melting-point metal as the top electrode in an AlScN-based ferroelectric memory device and performing annealing treatment to form a ferroelectric overlay, the problems of high operating voltage and large leakage current are solved, significant voltage and leakage current reductions are achieved, and promotion of device development.
Patent Information
- Application Number
- CN202411483386.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-21
AI Technical Summary
The existing AlScN-based ferroelectric memory devices have problems with high operating voltage and large leakage current, which limits their further development and industrialization.
Using a low -melting point metal with a melting point below 200 ° C, such as IN, SN, and common crystal welding, as a top electrode, and through low temperature annealing treatment, the low melting point metal diffusion and penetration into the functional layer, forming iron or more than four yuan or more iron. Electric overlapping layer.
It significantly reduces the operating voltage and leakage current of AlScN-based ferroelectric memory devices, improves the electrical properties of the functional layer, and promotes the development of AlScN-based ferroelectric memories.
Smart Images

Figure CN119342839A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor technology, and in particular to an AlScN device with low operating voltage and low leakage current and a preparation method thereof. Background Art
[0002] Ferroelectric memory is a non-volatile memory that uses the two different orientations (N-polarization and M-polarization) of the spontaneous polarization of ferroelectric thin film materials in an electric field as logic units to store data. It has the advantages of high-speed reading and writing, high-density integration, and radiation resistance. The most critical part of the memory is its storage unit, which determines the integration and read-write performance of the memory. For ferroelectric memory, its storage unit is generally a ferroelectric capacitor structure. Therefore, whether high-quality ferroelectric films can be grown to make ferroelectric capacitors is the key to improving the performance of ferroelectric memory. The current mainstream ferroelectric films include PZT, HfO2, etc. These ferroelectric films have problems such as poor stability and incompatibility with CMOS processes, so it is urgent to find a new type of ferroelectric film.
[0003] III-nitride semiconductors such as AlN, GaN, and InN have unique properties such as large bandgap, high breakdown electric field, large thermal conductivity, high electron saturation drift velocity, and small dielectric constant, which make them show great potential in optoelectronic devices, power electronics, radio frequency microwave devices, lasers, and detection devices. Sc-doped III-nitride semiconductors also have excellent piezoelectric and ferroelectric properties. In 2019, Akiyama et al. proved that AlScN has ferroelectricity, which is obtained by Sc-doped wurtzite-structured AlN, which has opened up a new path for the development of ferroelectric memory. AlN has excellent physical properties such as high resistivity, high thermal conductivity, high stability, and high acoustic wave transmission rate, and is a widely used piezoelectric material. It is generally believed that when the applied electric field strength of AlN is less than the breakdown electric field strength of the AlN thin film medium, polarization reversal cannot be performed, so AlN cannot exhibit ferroelectricity. The doping of Sc reduces the energy barrier between the two polarization states of AlN, N polarization and M polarization, so its polarization conversion electric field strength is reduced and lower than the breakdown electric field strength, thus showing ferroelectricity. This discovery makes it possible for AlScN ferroelectric films to be used as ferroelectric memory. AlScN-based ferroelectric films have high residual polarization strength and coercive field that are difficult to achieve with other ferroelectric materials. Its preparation process is also compatible with CMOS technology and has high temperature stability, which meets the requirements of new ferroelectric memory.
[0004] In AlScN-based ferroelectric memory, the selection and processing of electrode materials are of utmost importance. AlScN-based ferroelectric memory using different metal electrodes has different operating voltages, and the processing method of the electrode determines the quality of the interface relationship between the electrode and the functional layer, which also directly affects the operating voltage and leakage current of AlScN-based ferroelectric memory devices. At present, the mainstream electrodes used in AlScN-based ferroelectric memory are Pt, Mo and TiN, etc., but AlScN-based ferroelectric memory using these materials has two serious scientific problems, one is high operating voltage, and the other is large leakage current. These two scientific problems are also key factors restricting its further development. Summary of the invention
[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide an AlScN device with low operating voltage and low leakage current and a preparation method thereof.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: In a first aspect, the present invention provides an AlScN ferroelectric thin film device with low operating voltage and low leakage current, comprising a bottom electrode layer, a functional layer and a top electrode layer stacked in sequence; the functional layer comprises an AlScN ferroelectric material, and the bottom electrode layer is in ohmic contact with the functional layer; the material of the top electrode layer comprises a low melting point metal having a melting point lower than 200°C.
[0007] Furthermore, a portion of the low melting point metal element diffuses and penetrates into the functional layer to form a quaternary or higher ferroelectric stacked layer.
[0008] In a second aspect, the present invention further provides a method for preparing an AlScN ferroelectric thin film device with low operating voltage and low leakage current, comprising: forming a bottom electrode layer; Depositing a functional layer on the surface of the bottom electrode layer, wherein the functional layer comprises an AlScN ferroelectric material; Forming a top electrode layer on the surface of the functional layer, wherein the material of the top electrode layer includes a low melting point metal with a melting point lower than 200° C., to obtain the AlScN ferroelectric thin film device; And optionally, the AlScN ferroelectric thin film device is annealed to allow the low melting point metal to diffuse and penetrate into the functional layer.
[0009] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include: The AlScN ferroelectric thin film device and the preparation method thereof provided by the present invention can significantly reduce the operating voltage and leakage current thereof by setting a low melting point metal as a top electrode, and preferably, the low melting point metal is melted and diffused and infiltrated into the functional layer through annealing treatment, so as to form a good contact and infiltration doping with the functional layer, thereby forming a deep modification of the electrical characteristics of the functional layer. The top electrode is not only used as an electrode, but also as a doping modification material layer. Specifically, the diffusion and infiltration of the low melting point metal forms a ferroelectric superposition layer of a quaternary or higher system, so that the operating voltage and leakage current of the AlScN-based ferroelectric memory device can be further reduced at the same time, which has far-reaching significance for the development of AlScN-based ferroelectric memory.
[0010] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a schematic diagram of the preparation process of an AlScN device provided by a typical implementation case of the present invention; Figure 2a This is a PUND test diagram of an AlScN device provided by a typical comparative example of the present invention; Figure 2b It is a PUND test diagram of an AlScN device provided by a typical implementation case of the present invention; Figure 3 It is a schematic diagram of an annealing temperature curve in a preparation process of an AlScN device provided in a typical implementation case of the present invention; Figure 4 This is a PUND test diagram of an AlScN device after annealing provided by a typical implementation case of the present invention. DETAILED DESCRIPTION
[0012] Existing AlScN-based ferroelectric memory devices generally have problems with high operating voltage and large leakage current, which directly affect the further development and industrialization of AlScN-based ferroelectric memory devices. Currently, the main way to solve the high operating voltage is to reduce the film thickness, but this method will bring greater leakage current and also affect the ferroelectricity of the device.
[0013] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.
[0014] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0015] An embodiment of the present invention provides an AlScN ferroelectric thin film device with low operating voltage and low leakage current, comprising a bottom electrode layer, a functional layer and a top electrode layer stacked in sequence; the functional layer comprises an AlScN ferroelectric material, and the bottom electrode layer is in ohmic contact with the functional layer; the material of the top electrode layer comprises a low-melting-point metal with a melting point lower than 200°C, and a part of the low-melting-point metal element diffuses and penetrates into the functional layer to form a quaternary or higher ferroelectric stacking layer.
[0016] In order to solve the above-mentioned problems, the present invention essentially proposes an electrode material design and processing method for reducing the voltage of AlScN ferroelectric thin film, that is, using low-melting-point metals such as In, Sn and eutectic solder as the top electrode of AlScN-based ferroelectric memory, and preferably performing low-temperature annealing treatment on it so that the low-melting-point metal can melt and diffuse and penetrate into the functional layer.
[0017] The key technical means in the above technical scheme are: 1. By selecting low-melting-point metals such as In, Sn and eutectic solder, and subjecting them to low-temperature annealing treatment, they are melted and diffused into the AlScN layer to form a thin layer of quaternary ferroelectric film, which forms an overlay layer with the main AlScN layer. Specifically, if the low-melting-point metal is selected as a metal element, a quaternary system of AlScN plus the metal is formed. If the low-melting-point metal is selected as an alloy of these metal elements, a new overlay film system of five or more elements is formed; this can reduce the operating voltage of the device. 2. Unlike the contact between other metal electrodes and the AlScN layer, the low-melting-point metal electrode after annealing has better contact, which greatly reduces the leakage current of the device.
[0018] In the prior art, there are some technical solutions that adopt the technical idea of annealing the assembly after the electrode and the semiconductor layer are in contact to form a good ohmic contact between the electrode and the semiconductor layer, thereby significantly reducing the contact resistance of the electrode. However, this type of technical solution of the present invention is not consistent. The improvement principle based on the present invention is not to reduce the contact resistance, but to change the electrical properties of the functional layer itself through the contact and diffusion of the low-melting-point metal and the functional layer, thereby achieving a significant reduction in the flip voltage (based on U=I×R, under a relatively weak working current, the voltage division at the electrode contact resistance is limited, so the simple reduction of the contact resistance will not have much effect on the flip voltage of the device).
[0019] Therefore, regarding some specific composition and structural details, in some embodiments, the material of the top electrode layer includes any one or a combination of two or more of metal In, metal Sn, and eutectic solder. However, it is not limited to this, and metal electrodes with low melting point characteristics and capable of diffusing into the functional layer are all within the feasible range.
[0020] In some embodiments, along the stacking direction, the structure of the functional layer includes any one of AlN buffer layer / AlScN sublayer / AlN buffer layer, AlN buffer layer / AlScN sublayer, AlScN sublayer / AlN buffer layer or a single AlScN layer.
[0021] In some embodiments, the thickness of the AlScN sublayer is 10-500 nm, and the thickness of the AlN buffer layer is 1-50 nm.
[0022] As for the specific structure of the bottom electrode, in some embodiments, the bottom electrode layer includes a contact layer and a current collecting layer; the contact layer is in direct contact with the functional layer, and the current collecting layer is stacked with the contact layer to serve as a current collector of the contact layer.
[0023] In some embodiments, the material of the contact layer includes any one of TiN, Pt, and Mo with a 111 crystal plane.
[0024] In some embodiments, the material of the current collecting layer includes any one of Ni and Au or a combination of two or more thereof.
[0025] In addition, with respect to the overall device structure, in some embodiments, in the planar direction perpendicular to the stacking direction, the size of the functional layer is smaller than that of the bottom electrode layer, and the size of the top electrode layer is smaller than that of the functional layer; and when observed in the stacking direction, the edge of the functional layer and the edge of the bottom electrode layer have a spacing distance, and the edge of the top electrode layer and the edge of the functional layer have a spacing distance.
[0026] In some embodiments, the functional layers and their corresponding top electrode layers are disposed in multiple groups on the bottom electrode layer.
[0027] Corresponding to the structural design of the above device, a second aspect of the embodiment of the present invention further provides a method for preparing an AlScN ferroelectric thin film device with low operating voltage and low leakage current, which comprises the following steps: forming a bottom electrode layer; Depositing a functional layer on the surface of the bottom electrode layer, wherein the functional layer comprises an AlScN ferroelectric material; A top electrode layer is formed on the surface of the functional layer. The material of the top electrode layer includes a low melting point metal with a melting point below 200° C., thereby obtaining a device precursor. The precursor structure has the characteristics of low operating voltage and low leakage current, and can be used as an AlScN ferroelectric thin film device.
[0028] Furthermore, in order to further increase the doping degree, the device precursor may be selectively annealed to allow the low melting point metal to diffuse and penetrate into the functional layer to obtain the AlScN ferroelectric thin film device.
[0029] In some embodiments, the annealing treatment is performed at a temperature of 150-400° C. and for a time of 1-60 min.
[0030] As some typical implementation cases of the above technical solution, a method of preparing an AlScN ferroelectric memory device by pulsed laser deposition (PLD) and reducing the device operating voltage by using a low-melting-point metal electrode and annealing it is exemplified.
[0031] The traditional preparation process of AlScN ferroelectric thin film devices is as follows: Figure 1 As shown, the device and preparation method provided by the present invention are different from the device and preparation method provided by the present invention mainly in that the material and preparation method of the top electrode are different. Specifically, the traditional preparation method includes the following steps: (1) Prepare the substrate and perform organic cleaning.
[0032] (2) Cover half of the cleaned substrate with a metal strip and fix it to the sample holder for electron beam evaporation with high-temperature tape. Use electron beam evaporation to deposit a metal current collector layer.
[0033] (3) Use a metal strip to block half of the grown current collector layer and place them together on the PLD sample holder. Use a metal clip to fix the substrate and the metal strip, and place them in the epitaxial chamber to start growing the contact layer. The current collector layer and the contact layer serve as the bottom electrode. Ensure that part of the grown contact layer is in contact with the current collector layer, and the other part is exposed from the current collector layer. This design can facilitate the subsequent testing of thin film devices.
[0034] (4) Take out the sample, remove the metal strip and replace the metal mask and repeat the steps in (3) to place the sample into the epitaxial chamber and start growing the functional layer.
[0035] (5) After growth and in-situ annealing, remove the sample and replace the mask. Align the mask with the sample and fix them to the sample holder dedicated to electron beam evaporation with high-temperature tape. Use electron beam evaporation to sequentially deposit Ti and / or Au top electrodes.
[0036] The preparation process of the AlScN ferroelectric thin film device with In electrode illustrated in some implementation cases of the present invention is basically the same as the device preparation process of the two electrodes described above. The top electrode in step (5) is replaced with 1 μm In metal grown by thermal evaporation, and the size remains unchanged, to prepare an AlScN ferroelectric thin film device with TiN as the bottom electrode and In as the top electrode. The device has shown lower operating voltage and leakage current than traditional devices.
[0037] In order to further reduce the operating voltage and leakage current, the device can be annealed to allow the top electrode to diffuse and penetrate.
[0038] Specifically, the method for preparing AlScN-based ferroelectric memory devices can be PLD, magnetron sputtering, molecular beam epitaxy (MBE), metal organic compound vapor phase epitaxy (MOCVD), atomic layer deposition (ALD), etc., and is not limited thereto. The low melting point metal used as the top electrode can be In, or Sn, eutectic solder, etc., with a melting point of less than 200°C or an alloy. The substrate material in step (1) can be sapphire, Si, GaN, glass, etc., which are commonly used substrate materials, and the substrate can be of any size. The conductive metal in step (2) can be 20nm Ni and 100nm Au, or conductive metal of any thickness. The growth method can be electron beam evaporation, magnetron sputtering, thermal evaporation, etc. Of course, even if the above-mentioned collector layer metal is not formed, but connected by other electrical connection methods, the equivalent effect can also be achieved. The thickness of the TiN (111) bottom electrode in step (3) can be 20nm-200nm. The type of the contact layer in the bottom electrode can also be Pt (111) or Mo (111), etc. The functional layer in step (4) can be AlN / AlScN / AlN, or AlN / AlScN, AlScN / AlN, or a single layer of AlScN, wherein the thickness of AlScN can be 10nm-500nm, and the thickness of AlN can be 1nm-50nm. The side length of the functional layer can be 100nm-1cm. The temperature for low-temperature annealing of the low-melting-point metal electrode can be 150°C-400°C, and the annealing time can be 1min-60min.
[0039] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.
[0040] Example 1 This embodiment illustrates a preparation process of an AlScN ferroelectric thin film device with low operating voltage and low leakage current, which is specifically as follows: (1) Prepare a 15 mm × 15 mm cut sapphire substrate for organic cleaning.
[0041] (2) Cover half of the cleaned sapphire substrate with a metal strip and fix it to the sample holder for electron beam evaporation with high-temperature tape. Deposit 20nm of Ni and 100nm of Au by electron beam evaporation.
[0042] (3) Block half of the grown Ni / Au with a metal strip, place them together on the PLD sample holder, fix the substrate and the metal strip with a metal clip, and place them in the epitaxial chamber to start growing a 20nm TiN bottom electrode. The growth parameters of TiN are shown in Table 1 (of course, the process conditions during the specific preparation can be adjusted appropriately and are not limited to the scope of the examples in the present invention). Ensure that the grown TiN is partially in contact with Ni / Au. This design can facilitate the subsequent testing of thin film devices.
[0043] Table 1 Growth process parameters of TiN electrode and AlN buffer layer
[0044] (4) Take out the sample, remove the metal strip and place the metal mask on it and repeat the steps in (3) to put the sample into the epitaxial chamber and start growing the functional layer. The functional layer is an AlN / AlScN / AlN structure. The thickness of the AlScN ferroelectric film is 50nm, and the thickness of the AlN film is 20nm. The functional layer is a square with a side length of 500μm.
[0045] (5) After the growth and in-situ annealing are completed, the sample is taken out and the mask is replaced. After aligning the mask with the sample, fix it to the sample holder dedicated to electron beam evaporation with high-temperature tape. Use electron beam evaporation to evaporate a 120nm In electrode. It should be noted that the evaporated In top electrode should be completely on the AlScN ferroelectric film to form a "U"-shaped structure, with the top electrode in the inner circle and the functional layer in the outer circle to prevent the top electrode from being directly connected to the bottom electrode. Among them, the top electrode is a square with a side length of 100μm.
[0046] Comparative Example 1 This comparative example is substantially the same as the above-mentioned Example 1, except that: In step (5), 20 nm Ti and 100 nm Au are sequentially deposited by electron beam evaporation. It should be noted that the deposited Ti / Au top electrode should be completely on the AlScN ferroelectric film to form a "U"-shaped structure to prevent the top electrode from being directly connected to the bottom electrode. The top electrode is a square with a side length of 100 μm.
[0047] like Figure 2a and Figure 2b As shown, Figure 2a The interval time (delay time) between pulses of AlScN-based ferroelectric thin film device samples with TiN and Ti / Au as upper and lower electrodes d, Pulse maximum voltage output time t p The time required for the pulse voltage to rise to the maximum voltage is t rf Both are 1×10 -4 The interval time between pulses in the sample with TiN bottom electrode and In top electrode in Figure (b) is t d , Pulse maximum voltage output time t p The time required for the pulse voltage to rise to the maximum voltage is t rf Both are 3×10 -4 seconds. Figure 2a It can be seen that the voltage applied when the polarization reversal current signal appears is 13.5V. Figure 2b It can be clearly seen that when the applied voltage is 12V, the current signal excited by the P pulse and the N pulse is obviously larger than the current signal excited by the U pulse and the D pulse, and the extra current signal is the polarization current. This shows that under a voltage of 12V, the AlScN-based ferroelectric thin film device with In as the top electrode has a polarization reversal current signal. After comparison, it is not difficult to find that the operating voltage of the AlScN-based ferroelectric thin film device with In as the top electrode is lower than that of the device with TiN as the top electrode. This further proves the previous assumption, that is, when depositing the top electrode, the doping of In helps to reduce the operating voltage of the AlScN-based ferroelectric thin film device.
[0048] Example 2 This embodiment continues to perform annealing treatment on the basis of embodiment 1, as shown below: The AlScN ferroelectric thin film device with In top electrode prepared in Example 1 was subjected to low temperature annealing. We used a rapid annealing furnace to anneal the AlScN ferroelectric thin film devices grown with different electrodes. The annealing temperature was 250°C and the annealing time was 5 minutes. The heating curve is as follows: Figure 3 As shown, nitrogen protection was used throughout the annealing process.
[0049] like Figure 2b and 4 As shown, Figure 2b This is the PUND test diagram of the In electrode AlScN-based ferroelectric thin film device before annealing. Figure 4 This is the PUND test diagram of the In electrode AlScN-based ferroelectric thin film device after annealing, where Figure 2b This has been discussed in detail in the previous article and will not be repeated here. Figure 4 It can be seen that when the applied voltage is 9V, the current signal excited by the P pulse is greater than the current signal excited by the U pulse, indicating that there is a polarization current signal under this voltage, which can cause polarization reversal. Figure 2bBy comparison, it can be seen that after low-temperature annealing, the polarization reversal voltage is reduced from 12V to 9V, indicating that the In electrode treated with low-temperature annealing has a very significant effect on reducing the operating voltage of AlScN-based ferroelectric thin film devices.
[0050] In addition, you can Figure 2b It can be seen that the current signals stimulated by the N pulse and the D pulse are very weak. This may be because the In top electrode forms a good contact with the upper AlN layer of the functional layer after annealing, while the bottom electrode TiN does not contact the lower AlN layer of the functional layer well enough, and the upper and lower electrodes are of different types. These combined reasons lead to this "asymmetric" phenomenon.
[0051] In summary, it can be concluded that low-temperature annealing of the In electrode can significantly reduce the operating voltage of AlScN-based ferroelectric thin film devices. This discovery is of great help to the development of AlScN-based ferroelectric thin film devices.
[0052] In general, compared with the devices with TiN and Ti / Au electrodes, the low melting point In electrode has a significant effect on reducing the operating voltage of AlScN-based ferroelectric thin film devices from 13.5V to 12V, and after low-temperature annealing at 250°C, the operating voltage is further reduced to 9V. This discovery provides a strong guarantee for the development of subsequent work, and this discovery is also expected to solve the major scientific problems encountered by AlScN-based ferroelectric memory devices, which is crucial to the development of AlScN-based ferroelectric memory devices.
[0053] Comparative Example 2 This comparative example is similar to Example 2, except that: The device with Ti / Au electrodes prepared in Comparative Example 1 was subjected to low-temperature annealing, high-temperature annealing and low-temperature long-term annealing respectively, so that Ti can also effectively diffuse into the functional layer.
[0054] The low-temperature annealing is carried out under the same conditions as those in Example 2, the high-temperature annealing refers to raising the annealing temperature to 500° C., and the low-temperature long-term annealing refers to maintaining the annealing temperature but extending the annealing time to 10 h.
[0055] In this comparative example, it can be found that no matter what annealing method is adopted, even if the diffusion degree is increased by increasing the temperature and prolonging the time, the diffusion and penetration of Ti does not change the operating voltage and leakage current of the above device.
[0056] This shows that the technical principle on which the present invention is based is the melting, diffusion and doping of the selected low-melting-point metal on the surface of the functional layer, rather than simply the improvement in contact performance brought about by the diffusion of any metal electrode material.
[0057] Example 3 This embodiment is substantially the same as Embodiments 1 and 2, with the main differences being: The material of the top electrode is replaced with Sn, and the rest of the preparation process and device structure and size remain unchanged.
[0058] The operating voltage of the device finally obtained is still significantly lower than that of the traditional device, and the leakage current is also at an extremely low level comparable to that of the above-mentioned embodiment.
[0059] Example 4 This embodiment is substantially the same as Embodiments 1 and 2, with the main differences being: The AlN in the upper layer of the functional layer is omitted to form an AlN / AlScN functional layer, and the rest of the preparation process and device structure and size remain unchanged.
[0060] The operating voltage of the device finally obtained is still significantly lower than that of the traditional device, and the leakage current is also at an extremely low level comparable to that of the above-mentioned embodiment.
[0061] Example 5 This embodiment is substantially the same as Embodiments 1 and 2, with the main differences being: The AlN layer in the lower layer of the functional layer is omitted to form an AlScN / AlN functional layer, and the rest of the preparation process and device structure and size remain unchanged.
[0062] The operating voltage of the device finally obtained is still significantly lower than that of the traditional device, and the leakage current is also at an extremely low level comparable to that of the above-mentioned embodiment.
[0063] Example 6 This embodiment is substantially the same as Embodiment 2, and the main difference is that: Change the annealing conditions, annealing temperature is 400℃, time is 1min.
[0064] The operating voltage and leakage current characteristics of the device finally obtained are basically consistent with those of Example 2.
[0065] Example 7 This embodiment is substantially the same as Embodiment 2, and the main difference is that: Change the annealing conditions, annealing temperature is 150℃, time is 60min.
[0066] The operating voltage and leakage current characteristics of the device finally obtained are basically consistent with those of Example 2.
[0067] In addition, the present invention also replaces the substrate and bottom electrode (current collecting layer and contact layer) in the above embodiments with materials of equivalent functions, and consistent experimental phenomena are observed, which significantly reduces the operating voltage and leakage current, and will not be elaborated here.
[0068] Based on the above embodiments and comparative examples, it can be clearly seen that the AlScN ferroelectric thin film device and the preparation method thereof provided in the embodiments of the present invention can significantly reduce its operating voltage and leakage current by setting a low-melting-point metal as the top electrode, and preferably melt the low-melting-point metal through annealing treatment and diffuse and penetrate into the functional layer to form good contact and doping with the functional layer, thereby forming a deep modification of the electrical properties of the functional layer. The top electrode not only serves as an electrode, but also as a doping-modified material layer, which can further reduce the operating voltage and leakage current of the AlScN-based ferroelectric memory device at the same time, which has far-reaching significance for the development of AlScN-based ferroelectric memory.
[0069] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. An AlScN ferroelectric thin film device with low operating voltage and low leakage current, comprising a bottom electrode layer, a functional layer and a top electrode layer stacked in sequence; the functional layer comprises AlScN ferroelectric material, and the bottom electrode layer is in ohmic contact with the functional layer; It is characterized in that The material of the top electrode layer includes a low melting point metal with a melting point lower than 200° C., and a part of the low melting point metal element diffuses and penetrates into the functional layer to form a quaternary or higher ferroelectric stacked layer.
2. The AlScN ferroelectric thin film device according to claim 1, characterized in that: The material of the top electrode layer includes any one of metal In, metal Sn, and eutectic solder, or a combination of two or more thereof.
3. The AlScN ferroelectric thin film device according to claim 1, characterized in that: Along the stacking direction, the structure of the functional layer includes any one of AlN buffer layer / AlScN sublayer / AlN buffer layer, AlN buffer layer / AlScN sublayer, AlScN sublayer / AlN buffer layer or a single AlScN layer.
4. The AlScN ferroelectric thin film device according to claim 3, characterized in that: The thickness of the AlScN sublayer is 10-500 nm, and the thickness of the AlN buffer layer is 1-50 nm.
5. The AlScN ferroelectric thin film device according to claim 1, characterized in that: The bottom electrode layer includes a contact layer and a current collecting layer; the contact layer is in direct contact with the functional layer, and the current collecting layer is stacked with the contact layer to serve as a current collector for the contact layer.
6. The AlScN ferroelectric thin film device according to claim 5, characterized in that: The material of the contact layer includes any one of TiN, Pt, and Mo with a crystal plane of 111; And / or, the material of the current collecting layer includes any one of Ni and Au or a combination of two or more thereof.
7. The AlScN ferroelectric thin film device according to claim 1, characterized in that: In the planar direction perpendicular to the stacking direction, the size of the functional layer is smaller than that of the bottom electrode layer, and the size of the top electrode layer is smaller than that of the functional layer; and when observed in the stacking direction, the edge of the functional layer is spaced apart from the edge of the bottom electrode layer, and the edge of the top electrode layer is spaced apart from the edge of the functional layer.
8. The AlScN ferroelectric thin film device according to claim 7, characterized in that: The functional layers and the corresponding top electrode layers are arranged in multiple groups on the bottom electrode layer.
9. A method for preparing an AlScN ferroelectric thin film device with low operating voltage and low leakage current, characterized in that: include: forming a bottom electrode layer; Depositing a functional layer on the surface of the bottom electrode layer, wherein the functional layer comprises an AlScN ferroelectric material; Forming a top electrode layer on the surface of the functional layer, wherein the material of the top electrode layer includes a low melting point metal with a melting point lower than 200° C., to obtain the AlScN ferroelectric thin film device; And optionally, the AlScN ferroelectric thin film device is annealed to allow the low melting point metal to diffuse and penetrate into the functional layer.
10. The preparation method according to claim 9, characterized in that: The annealing treatment is carried out at a temperature of 150-400° C. and for a time of 1-60 min.
Citation Information
Cited By
Preparation method and preparation system of AlScN film
CN121931497A
Method for inhibiting leakage current of alscn ferroelectric capacitor memory based on weak base solution treatment
CN122641023A
Method for inhibiting leakage current of alscn ferroelectric capacitor memory based on weak base solution treatment
CN122641023B